Anastrozole when used as a superovulator, may alter key focal adhesion proteins associated with receptivity of uterine epithelial cells during implantation in the rat: a potential therapeutic clue in assisted reproductive technologies - Mwakikunga, Anthony Raphael. (My University, 2015)
Introduction: Anastrozole is clinically effective in ovulation induction, but it has not been well researched. The aim of this study was to determine the optimal dose for anastrozole as a superovulator and ascertain its effects on implantation in Wistar rats; also to determine its effects on uterine morphology during early pregnancy using light microscopy and scanning electron microscopy (SEM). [Abbreviated Abstract. Open document to view full version]
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy July, 2015
Keywords: Anastrozole; Superovulator; Receptivity of uterine; Epithelial cells; Implantation; Reproductive technologies